The Difference Between Old and New Intervention Effect to Decrease Pain on Frozen Shoulder - Pratama, A D; Dewi, N F (KnE Social Sciences, 2018)
Frozen shoulder is a pain resulting in limited range of motion (LGS) on the shoulder. It may arise because of a trauma, or gradually without signs or history of trauma. To deal with the pain in frozen shoulder, physiotherapy can provide modalities often used to reduce pain, that is, Transcutaneous Electrical Nerve Stimulation (TENS) and Short Wave diathermy (SWD). Besides modalities, there is also a new method that is Neuromuscular Taping (NMT) on the reduction of pain in patient’s frozen shoulder. NMT is a technique that involves applying elastic adhesive tape on the skin, provides local therapeutic effect and reduces pain. The difference between the effect of the provision of routine physiotherapy (TENS and SWD) and NeuroMuscular Taping (NMT) to a decrease in pain in cases of frozen shoulder. The type of research is an experimental approach to design Quasi-experimental study pre- and post-test two group design. Respondent of this study, as many as 20 people, were divided into two groups. Ten in the control group and 10 in the treatment group. The research was done twice a week for four week. Measurement pain do is Visual Analog Scale (VAS) with analysis techniques using Mann–Whitney Test. In the control group, the mean pre-test was 6.62 and post-test 5.74, while in the treatment group mean pre-test was 6.53 and post-test 4.24. Based on the statistics obtained through Mann–Whitney, available p-value = 0.0001. Different influences between physiotherapy routine and NMT to reduces pain. Keywords: frozen shoulder, pain, Transcutaneous Electrical Nerve Stimulation, short wave diathermy, NeuroMuscular Taping